Plan de comunicación: cultiva compromiso - Guzmán Martos, Diego Enrique (2023)
Given the hiring difficulties caused by the low motivation of temporary workers, the disconnection between work areas and the negative perception towards the company, an internal communication plan is proposed in order to solve the problem regarding lack of knowledge about the job on the crop fields and the lack of empathy towards temporary workers. This plan constitutes a strategy aimed at members of the administration and a motivation campaign aimed at temporary workers. This plan includes objectives, actions, indicators, and goals, as well as key messages and a schedule divided by audiences. Likewise, the communication pieces developed for the different channels and audiences to which this internal plan is directed are attached. The purpose of this plan is to improve the job retention of field workers in the short term and increase their job satisfaction. On the other hand, in the long term this plan seeks to improve the image of Campos Cultivados, create a culture of recognition, and encourage the loyalty of temporary workers.